Food and feed from legumes and oilseeds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Food and feed from legumes and oilseeds Edited by E Nwokolo and J Smartt 1995 440pp price UKL59.00 ISBN 0 41245 930 2